2003
DOI: 10.5694/j.1326-5377.2003.tb05198.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer knowledge and skills of interns in Australia and New Zealand in 2001: comparison with 1990, and between course types

Abstract: Objective: To compare the cancer knowledge and skills of interns in 2001 who graduated from graduate medical program (GMP) courses with those from non‐GMP courses, and to compare the cancer knowledge and skills of interns in 2001 with those who completed a similar survey in 1990. Design: Questionnaire survey of recently graduated interns in a random sample of Australian and New Zealand hospitals. The questionnaire was designed to allow direct comparison with the 1990 survey, and was guided by the Australian Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 8 publications
0
23
1
Order By: Relevance
“…In the above comparative study knowledge among students in the 1990s and 2000 from Australia, it was found the attendance in various multimodality clinics increased over a decade with increasing knowledge of multimodality therapy among undergraduates. [8] In the present study, no significant association was found between the number of classes attended and the self rated knowledge/confidence regarding role of radiotherapy and chemotherapy.…”
Section: Discussioncontrasting
confidence: 75%
“…In the above comparative study knowledge among students in the 1990s and 2000 from Australia, it was found the attendance in various multimodality clinics increased over a decade with increasing knowledge of multimodality therapy among undergraduates. [8] In the present study, no significant association was found between the number of classes attended and the self rated knowledge/confidence regarding role of radiotherapy and chemotherapy.…”
Section: Discussioncontrasting
confidence: 75%
“…During internship training, trainees learn clinical skills, perform clinical procedures, develop good clinical judgment, and acquire communication skills relevant to patient care 26. There exists wide intra78 and inter912 specialty variations in interns’ clinical knowledge and skills base. The variation is attributable to disparities in undergraduate training emphasis and availability of training resources113 and differences in interns’ attitudes to learning 3.…”
Section: Introductionmentioning
confidence: 99%
“…Previous surveys of the clinical knowledge and skills of medical interns have been dominated by assessments of their general medical skills;146912 skills in non-ophthalmic specialties,278 with only few studies1518 specifically evaluating ophthalmic knowledge and skills. The paucity of ophthalmology-specific surveys despite their established usefulness in generating critical feedback on undergraduate ophthalmic curriculum planning15 is disconcerting.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that although curricula introduced a new course material, it did not produce doctors with better knowledge about cancer. They pointed out that recent students have less exposure to cancer patients than those who trained 10 years ago [12]. Cave et al carried out a questionnaire for all 5,143 newly qualified doctors in UK in 2005.…”
Section: Discussionmentioning
confidence: 99%